2009
DOI: 10.1007/s00467-008-0972-1
|View full text |Cite
|
Sign up to set email alerts
|

Methylated arginine derivatives in children and adolescents with chronic kidney disease

Abstract: Asymmetric dimethylarginine (ADMA), a methylated L: -arginine (Arg) derivative is associated with endothelial dysfunction, vasoconstriction, and hypertension in animals and humans. We examined the relationship between these derivatives, estimated glomerular filtration rate (eGFR), and awake (AW) and asleep (AS) blood pressure (BP) load in children and adolescents (n = 28) with stage 2-3 chronic kidney disease (CKD) and in matched intra-familial controls (n = 10). Plasma L: -Arg, ADMA, and symmetric dimethylarg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
5
28
2
Order By: Relevance
“…The present results, however, are in good agreement with that previous study in that there was no association between BP abnormalities and ARG, ADMA, ARG-to-ADMA ratio, or ADMA-to-SDMA ratio. 40 Of significant interest is that the correlation between BP abnormalities and ARG-to-ADMA ratio or ADMA-to-SDMA ratio was not significant, which is inconsistent with our previous findings showing that plasma ARGto-ADMA ratio and ADMA-to-SDMA ratio are superior markers to predict hypertension in young SHR. 14 Given the fact that SHR is not a CKD-induced hypertension model, additional studies are needed across all insults of hypertension regarding the relationship between these markers and BP abnormalities in children.…”
Section: Discussioncontrasting
confidence: 83%
“…The present results, however, are in good agreement with that previous study in that there was no association between BP abnormalities and ARG, ADMA, ARG-to-ADMA ratio, or ADMA-to-SDMA ratio. 40 Of significant interest is that the correlation between BP abnormalities and ARG-to-ADMA ratio or ADMA-to-SDMA ratio was not significant, which is inconsistent with our previous findings showing that plasma ARGto-ADMA ratio and ADMA-to-SDMA ratio are superior markers to predict hypertension in young SHR. 14 Given the fact that SHR is not a CKD-induced hypertension model, additional studies are needed across all insults of hypertension regarding the relationship between these markers and BP abnormalities in children.…”
Section: Discussioncontrasting
confidence: 83%
“…After cleavage from the cell surface, suPAR is found in organic fluids (blood, saliva, cerebrospinal fluid, and urine) and takes part in various immunologic functions, including cell adhesion, migration, proteolysis, and tissue remodeling, among others (10,24,25). Our results of suPAR elevation in our patient cohorts with non-FSGS diagnoses might be explained by low-grade inflammation that is activated in children with certain forms of CKD (26). Our findings might be explained by results recently described by Wei and colleagues (27), which showed that C-reactive protein levels were low and did not correlate with serum suPAR levels in two large cohorts of patients with FSGS, thereby supporting the classification of FSGS as a noninflammatory disease.…”
Section: Discussionmentioning
confidence: 55%
“…However, others reported even a significant decrease in circulating ADMA levels in young diabetics with a mean age of 12 years and mean HbA 1c of 8.2 % (Huemer et al 2011). Comparably higher ADMA concentrations were also found in children with renal diseases (Lücke et al 2008;Brooks et al 2009;Wang et al 2007), in hypercholesterolemia (Hasanoğlu et al 2011), as well as in arterial hypertension (Sladowska-Kozłowska et al 2012) and pulmonary hypertension (Sanli et al 2012). The children examined in the present study did not have elevated concentrations of creatinine, cholesterol and triglycerides; also, they had no microalbuminuria, arterial hypertension or pulmonary hypertension (Table 1).…”
Section: Amino Acids Of the L-arg/no Pathwaymentioning
confidence: 75%
“…Other important factors to be considered in the discussion are the influence of renal function, glucose or insulin on the metabolism and elimination of ADMA (Vallance et al 1992;Cighetti et al 2009;Lajer et al 2009;Tarnow et al 2004). Like in adults, the circulating ADMA concentration has been shown to be elevated in children when renal function was impaired (Wang et al 2007;Lücke et al 2008;Brooks et al 2009). …”
Section: Amino Acids Of the L-arg/no Pathwaymentioning
confidence: 96%